DISCOVERY OF FOSSIL CERATOPHYLLUM DEMERSUM L. IN NORTHWEST TERRITORIES, CANADA - Terasmae, J.; Craig, B. G. (Canadian Journal of Botany, 1958)
Fossil Ceratophyllum demersum L. was discovered on sites east of Great Slave Lake, Northwest Territories, Canada. This distribution is both north and east of its presently known range. The palynological evidence supports the conclusion that the climate was warmer than the present when the silt, in which the fossil plant remains were found, was deposited. A radiocarbon age of 5400 ± 230 years (L-428) has been obtained for the sample.